حكم اختيار جنس الجنين في عمليات التلقيح الاصطناعي : دراسة مقارنة بين أحكام الفقه الإسلامي والقانون الجزائري - صالحي، سمية Salehi, Sumaya (جامعة قاصدي مرباح ورقلة - كلية الحقوق والعلوم السياسية, 2016)
This study showed what has been proven in practice, that infertility is no longer the only reason which pushes couples to request for artificial insemination, but remained extend to medical practices more than that and which ones to determine the sex of the fetus and choice, with the development of genetic engineering and biotechnology and other Sciences has led to the discover certain genetic diseases and trying to avoid it and change some genetic traits... which results the possibility of identifying and selecting the sex of the fetus, and since the reasons for resorting to determine the sex of the fetus are many and varied in a manner and choice cannot be with him set a standard and an officer in governing such practices all different reasons, the legality of this selection should be determined in accordance with the cause that leads to it; so you must find out the reasons for resorting to this process to a statement legitimate cases than others, and to indicate what is necessary and what without it.
بينت هذه الدراسة ما ثبت في الواقع العملي من أن العقم لم يعد هو السبب الوحيد الذي يقدم الأزواج من أجله على طلب التلقيح الاصطناعي، بل ظل يتسع ليشمل ممارسات طبية أكثر من ذلك والتي منها تحديد جنس الجنين واختياره، ومـع تطـور الهندسة الوراثية والبيوتكنولوجيا وغيرها من العلوم أدى إلى اكتشاف بعض الأمراض الوراثية والعمل على تجنبها وتغيير بعض الصفات الوراثية...مما نتج عنه إمكانية تحديد واختيار جنس الجنين، ولما كانت أسباب اللجوء إلى تحديد جنس الجنين واختيـاره متعددة ومتنوعة على نحو لا يمكن معه وضع معيار وضابط عام يحكم مثل هذه الممارسات جميعها على اختلاف أسبابها، فـإن مشروعية هذا التحديد والاختيار يجب أن تتحدد وفقا للسبب المؤدي إليه؛ لذا يجب معرفة الأسباب الداعية للجوء لهذه العملية لبيان الحالات المشروعة من غيرها، ولبيان ما هو ضروري وما دون ذلك.
Keywords: الفقه الإسلامي -- القوانين والتشريعات -- جنس الأجنة -- الإنجاب -- التلقيح الاصطناعي -- الجزائر